Konseling Teman Sebaya dengan Seni Kreatif Berbasis Kearifan Lokal untuk Meningkatkan Resiliensi Remaja Sekolah Menengah Pertama - Prasetiawan, Hardi; Wahyudi, Amien; Fauziah, Mufied (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2022)
This study aims to guide the implementation of Peer Counseling with Creative Arts based on local wisdom to increase resilience. The method used is development research. The instrument used is a scale using 2 forms, namely Scale I & Scale II. The results according tothis study clearly explain the application of Peer Counseling with Creative Arts based on Local Wisdom.